2021
DOI: 10.20377/jfr-365
|View full text |Cite
|
Sign up to set email alerts
|

The intergenerational transmission of loneliness between parents and their adult children

Abstract: Objective: This study examined the relationship between loneliness in parents and in their adult children, and took into account the role of gender differences in the intergenerational transmission of loneliness. Background: Although it is well documented that loneliness has negative effects on a person’s physical and mental health, only a relatively small number of empirical studies have investigated the intergenerational transmission of loneliness between parents and their children, including the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Parental loneliness was associated with 1.5–1.7 times higher odds of offspring loneliness in midlife, after controlling for age, sex, education, income, marital status or number of children. These findings are in line with previous studies reporting associations between parental and offspring loneliness 14 17 , 22 , although only one recent study examined the intergenerational transmission of loneliness in adult offspring 13 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Parental loneliness was associated with 1.5–1.7 times higher odds of offspring loneliness in midlife, after controlling for age, sex, education, income, marital status or number of children. These findings are in line with previous studies reporting associations between parental and offspring loneliness 14 17 , 22 , although only one recent study examined the intergenerational transmission of loneliness in adult offspring 13 .…”
Section: Discussionsupporting
confidence: 92%
“…Only relatively few studies have examined the potential association between loneliness in parents and in their offspring 13 . This is surprising, given that intergenerational processes underlying loneliness may have long-lasting negative consequences for health and wellbeing among both generations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the process of raising and educating their children, parents transmit both their own advantages and disadvantages to their children and influence their psychological and behavioral development [ 60 ]. The effects of parenting on offspring loneliness and stigma have been explored in previous studies [ 35 , 61 ]. However, the literature has not addressed the phenomenon of intergenerational transmission of loneliness stigma.…”
Section: Discussionmentioning
confidence: 99%
“…The present study is the first to analyze this phenomenon, reflecting certain innovative insights. In addition, previous research on the intergenerational transmission effect of loneliness has identified that mothers are more predictive of adult children than fathers [ 35 ]. In contrast, the present study reached inconsistent conclusions in the area of loneliness stigma.…”
Section: Discussionmentioning
confidence: 99%